1997
DOI: 10.1002/jlb.61.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against the human mannose receptor as a specific marker in flow cytometry and immunohistochemistry for macrophages

Abstract: Abstract:Recently we developed mouse monoclonal antibodies (inAb) against the isolated human 175-kDa mannose receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 29 publications
5
33
0
Order By: Relevance
“…Phagocytosis of unopsonized C. albicans by MØ has been shown to be mediated, to a considerable extent, by the MR; mannan and mannose-BSA inhibited 80% of C. albicans uptake by human monocyte-derived MØ (25) and murine peritoneal MØ. 2 The inhibition of sMR production by the matrix metalloprotease inhibitor BB 2116 strongly suggests a role for a metalloprotease in the release of sMR from the membrane. The matrix metalloproteases are a large family of extracellular zinc proteases, at least 18 distinct members of which have been discovered (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phagocytosis of unopsonized C. albicans by MØ has been shown to be mediated, to a considerable extent, by the MR; mannan and mannose-BSA inhibited 80% of C. albicans uptake by human monocyte-derived MØ (25) and murine peritoneal MØ. 2 The inhibition of sMR production by the matrix metalloprotease inhibitor BB 2116 strongly suggests a role for a metalloprotease in the release of sMR from the membrane. The matrix metalloproteases are a large family of extracellular zinc proteases, at least 18 distinct members of which have been discovered (28).…”
Section: Discussionmentioning
confidence: 99%
“…1 is a type I integral membrane glycoprotein expressed on many macrophage (MØ) subtypes, monocyte-derived dendritic cells, and hepatic endothelium (1)(2)(3)(4). MR is the founding member of a family of molecules sharing the same basic domain structure: an NH 2 -terminal cysteinerich domain; a fibronectin type II domain; and a variable number of C-type lectin carbohydrate recognition domains (CRDs), eight in the case of MR, followed by a transmembrane domain and a COOH-terminal intracellular domain (5)(6)(7).…”
Section: The Mannose Receptor (Mr)mentioning
confidence: 99%
“…Finally, based on the number of cells in involuting tissue that express macrophage mannose receptor and IL-13, a marker for M2 macrophages in humans and an M2-associated cytokine, we conclude that macrophages with an M2 phenotype are abundant in the human involuting mammary gland ( Figure 3H, arrows). 26,27,62 The breast tissues used for these studies were obtained from women who were subsequently diagnosed with cancer or found to be without evidence of malignancy. It might be anticipated that normal adjacent human breast tissue taken from the women with breast cancer would have higher levels of M2 macrophages present throughout the gland and, further, that these cases account for the higher levels of immune cells observed in the involuting human breast tissues depicted in Figure 3, D and E. First, in an attempt to minimize this confounder, lobules were taken from areas of the breast specimens that were morphologically normal but distinct from the tumor.…”
Section: Human Breast Involutionmentioning
confidence: 99%
“…The expression of MR is primarily restricted to tissue macrophages, myeloid DCs, and hepatic endothelial cells (33)(34)(35)(36), and as such makes an attractive candidate for targeting Ags to APCs. We generated a human anti-MR mAb, B11, by immunization of human Ig-expressing mice with immature human DCs, followed by standard hybridoma methodology.…”
Section: Characterization Of Anti-mr Mab B11mentioning
confidence: 99%